Konsep Wacana Global 'pembelajaran Seumur Hidup' Fakta dan Persepsi Peran untuk Dimainkan di Abad ke-21 dalam Dua Perspektif Barat dan Islam - Muhammad Budi Arif (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
Context The educational process which has no end or is called lifelong learning, Islam offers an integrative framework for achieving sustainable knowledge management and a holistic, integrated and balanced learning organization. This study aims to describe the concept of the global discourse 'lifelong learning' facts and role perceptions to be played in the 21st century in two western and Islamic perspectives. the conclusions of this study are: 1) In the western level lifelong learning is limited to utopia in the negotiation of the realization of education and political rationality from the institutional redesign which will be a site for contestation of different views on the meaning and application in global discourse whose application is influenced by the dynamics of the present , so that sometimes it loses the source of ideas and alternative practices that are strong and durable because they tend to be obscured by the author of a lifetime education itself. 2) Lifelong education from an Islamic perspective takes into account three dimensions of education in a holistic, integrated and balanced manner, each concept has a different focus area but remains in a holistic, integrated and balanced framework, Tarbiyah focuses on care and care in various stages of human development . Ta'dhib focuses on the ethical dimension on character development to produce highly moral individuals. Ta'lim pay attention to how knowledge is taught and learned.